Nanofibers with homogeneous heparin distribution and protracted release profile for vascular tissue engineering - Zhang, Hongmei; Zhang, Qilu; Du, Juan; Zhu, Tonghe; Chen, Dian; Liu, Feiying; Dong, Yang (Frontiers in Bioengineering and Biotechnology, 2023)
In clinic, the primary problem to be solved after small-diameter vessel grafts transplantation is how to control acute coagulation. The combination of heparin with high anticoagulant efficiency and polyurethane fiber with good compliance is the best choice for vascular materials. However, how to blend water-soluble heparin with fat-soluble poly(ester-ether-urethane)urea elastomer (PEEUU) uniformly and prepare nanofibers tubular grafts with uniform morphology is a huge challenge. In this research, we have compounded PEEUU with optimized constant concentration of heparin by homogeneous emulsion blending, then spun into the hybrid PEEUU/heparin nanofibers tubular graft (H-PHNF) for replacing rats’ abdominal aorta in situ for comprehensive performance evaluation. The results in vitro demonstrated that H-PHNF was of uniform microstructure, moderate wettability, matched mechanical properties, reliable cytocompatibility, and strongest ability to promote endothelial growth. Replacement of resected abdominal artery with the H-PHNF in rat showed that the graft was capable of homogeneous hybrid heparin and significantly promoted the stabilization of vascular smooth muscle cells (VSMCs) as well as stabilizing the blood microenvironment. This research demonstrates the H-PHNF with substantial patency, indicating their potential for vascular tissue engineering.